2014
DOI: 10.1016/j.ahj.2014.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Real-time use of instantaneous wave–free ratio: Results of the ADVISE in-practice: An international, multicenter evaluation of instantaneous wave–free ratio in clinical practice

Abstract: ObjectivesTo evaluate the first experience of real-time instantaneous wave–free ratio (iFR) measurement by clinicians.BackgroundThe iFR is a new vasodilator-free index of coronary stenosis severity, calculated as a trans-lesion pressure ratio during a specific period of baseline diastole, when distal resistance is lowest and stable. Because all previous studies have calculated iFR offline, the feasibility of real-time iFR measurement has never been assessed.MethodsThree hundred ninety-two stenoses with angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 22 publications
(30 reference statements)
1
27
1
1
Order By: Relevance
“…During the assessment of eligibility, further 6 studies were excluded. 8,[30][31][32][33][34] Finally, a total of 23 studies were available for the analysis, 7,[9][10][11][12][13][14][15][16][17][18][19][20][21]28,29,[35][36][37][38][39][40][41] including 6381 stenoses. The study selection procedure is reported in details in Figure 1 while the Table summarizes the most relevant characteristics of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…During the assessment of eligibility, further 6 studies were excluded. 8,[30][31][32][33][34] Finally, a total of 23 studies were available for the analysis, 7,[9][10][11][12][13][14][15][16][17][18][19][20][21]28,29,[35][36][37][38][39][40][41] including 6381 stenoses. The study selection procedure is reported in details in Figure 1 while the Table summarizes the most relevant characteristics of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…ADVISE-In-Practice was the first study to use the commercially available iFR console. 66 In this international, multicenter study of 392 stenoses in 313 patients, iFR had a high classification match with FFR (80% using the FFR 0.80 cut-point; 88% with ischemic threshold of 0.75 and 92% if the FFR gray-zone was accounted for). 66 Using the hybrid approach, 61% of the patients could be spared from adenosine, with a Figure 7.…”
Section: Clinical Application Of Ifr: Using the Ifr-ffr Hybrid Approachmentioning
confidence: 99%
“…ACS, acute coronary syndrome; FFR, fractional flow reserve; iFR, instantaneous wave-free ratio; PCI, percutaneous coronary intervention. Reproduced with permission from Petraco R, et al 66 Current Developments in Pressure-Only Indices stenoses in 82 patients with ACS and stable disease, an iFR threshold of 0.92 best matched an FFR of 0.80 with a diagnostic concordance with FFR of 81.3%. 71 No difference in diagnostic efficiency between ACS patients and those with stable disease was found and all apparent discrepancies were within the FFR 0.75-0.80 gray-zone.…”
Section: Clinical Application Of Ifr: Using the Ifr-ffr Hybrid Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…34, 35 Notably, distal to corointermediate coronary stenoses (Figure 2). 30 For a FFR cutoff of 0.80, a predefined iFR value of 0.90 provided the optimal cutoff, with a classification match of 80%; when the originally validated 0.75 ischemic FFR cutoff was used as a reference comparison, the agreement between iFR and FFR increased to 88% with the optimal iFR cutoff being 0.85; when accounting for the known 0.75-0.80 FFR gray zone, the classification match between iFR and FFR increased to 93%. Finally, confirming previous reports, 31 a hybrid decision-making strategy with iFR and FFR could avoid the use of vasodilator in 61% of patients, while maintaining 94% overall agreement with FFR classification of lesions.…”
Section: Niccoli G Et Almentioning
confidence: 99%